2010
DOI: 10.1115/1.4001311
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of CFD Based Hemodynamic Results in Rabbit Aneurysm Models to Idealizations in Surrounding Vasculature

Abstract: Computational fluid dynamics (CFD) studies provide a valuable tool for evaluating the role of hemodynamics in vascular diseases such as cerebral aneurysms and atherosclerosis. However, such models necessarily only include isolated segments of the vasculature. In this work, we evaluate the influence of geometric approximations in vascular anatomy on hemodynamics in elastase induced saccular aneurysms in rabbits. One representative high aspect ratio (AR—height/neck width) aneurysm and one low AR aneurysm were cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 38 publications
1
16
0
Order By: Relevance
“…In a study of 51 elastase induced RCCA aneurysms, Zeng et al found that the range in values of pressure, wall shear stress, and oscillatory shear index were all within the ranges seen in human aneurysms. The number of recirculation regions seen within the aneurysms was also similar to that seen in human aneurysms 31 32…”
Section: Aneurysm Hemodynamicssupporting
confidence: 66%
“…In a study of 51 elastase induced RCCA aneurysms, Zeng et al found that the range in values of pressure, wall shear stress, and oscillatory shear index were all within the ranges seen in human aneurysms. The number of recirculation regions seen within the aneurysms was also similar to that seen in human aneurysms 31 32…”
Section: Aneurysm Hemodynamicssupporting
confidence: 66%
“…Animal models commonly used for clinical studies are good for testing medical devices and investigating hemodynamics 71 but are generally biologically deficient. On the other hand, current endogenous models 34,37 capture some hemodynamic-biologic effects in the early stages of aneurysm formation but lack the ability to study growth and rupture.…”
Section: Future Directionsmentioning
confidence: 99%
“…Suspended particles and nonNewtonian effect of the fluid were ignored. The vessel walls were taken as rigid, an assumption frequently employed in CFD analysis of blood flow (Shojima et al, 2004;Zeng et al, 2010). Effects of relaxing these assumptions can be investigated, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, quantitative information is provided to the clinicians to assess if such a repair is necessary. The precise selection of vasculature geometry is critical, as computational accuracy might be compromised if insufficient neighboring blood vessels are included in the calculations (Zeng et al, 2010). Here we tested the robustness of our results against variation in domain geometry in two ways.…”
Section: Geometric Configurationmentioning
confidence: 99%